Biofunctionalization of Polyoxometalates with DNA Primers, Their Use in the Polymerase Chain Reaction (PCR) and Electrochemical Detection of PCR Products. Issue 49 (22nd October 2015) - Debela, Ahmed M.; Ortiz, Mayreli; Beni, Valerio; Thorimbert, Serge; Lesage, Denis; Cole, Richard B.; O'Sullivan, Ciara K.; Hasenknopf, Bernold
Abstract: The bioconjugation of polyoxometalates (POMs), which are inorganic metal oxido clusters, to DNA strands to obtain functional labeled DNA primers and their potential use in electrochemical detection have been investigated. Activated monooxoacylated polyoxotungstates [SiW11 O39 Sn(CH2 )2 CO] 8− and [P2 W17 O61 Sn(CH2 )2 CO] 6− have been used to link to a 5′‐NH2 terminated 21‐mer DNA forward primer through amide coupling. The functionalized primer was characterized by using a battery of techniques, including electrophoresis, mass spectrometry, as well as IR and Raman spectroscopy. The functionality of the POM‐labeled primers was demonstrated through hybridization with a surface‐immobilized probe. Finally, the labeled primers were successfully used in the polymerase chain reaction (PCR) and the PCR products were characterized by using electrophoresis. Abstract : Hybrid detection : In a new role for polyoxometalates (POMs), these inorganic polyanions are covalently linked to DNA primers, the DNA strands are elongated by the polymerase chain reaction (PCR), and the POM–DNA hybrids are detected electrochemically after hybridization to surface‐tethered probes (see figure). Thus, polyoxometalates are new versatile redox labels for bioanalysis.